2003
DOI: 10.1007/s00421-002-0763-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endurance training and acute exercise on sarcoplasmic reticulum function in rat fast- and slow-twitch skeletal muscles

Abstract: Following 10 weeks of endurance training and in age-matched sedentary rats, sarcoplasmic reticulum (SR) Ca(2+)-uptake, Ca(2+)-release, and Ca(2+)-stimulated adenosinetriphosphatase (ATPase) activity were examined in homogenates of the plantaris and soleus muscles from rats subjected to moderate-intensity treadmill running to exhaustion. In order to examine the effects of acute exercise and/or training on SR Ca(2+)-handling capacity, comparisons between exhausted and non-exercised rats and between trained and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…Thus, we have previously demonstrated that high-intensity training induced an enhanced peak SR Ca 2+ release, due to an enhanced total volume of SR, whereas SR Ca 2+ sequestration function was not altered (Ørtenblad et al 2000b). However, SR function is depressed to a similar extent with fatigue in trained and untrained subjects, despite that trained subjects exercise at a higher intensity or longer (Inashima et al 2003;Li et al 2002), indicating that training may delay the exercise-induced progressive deterioration of SR function. However, little is known about the eVect of a soccer match on SR function and the recovery of the SR system in the days after a match.…”
Section: Introductionmentioning
confidence: 70%
“…Thus, we have previously demonstrated that high-intensity training induced an enhanced peak SR Ca 2+ release, due to an enhanced total volume of SR, whereas SR Ca 2+ sequestration function was not altered (Ørtenblad et al 2000b). However, SR function is depressed to a similar extent with fatigue in trained and untrained subjects, despite that trained subjects exercise at a higher intensity or longer (Inashima et al 2003;Li et al 2002), indicating that training may delay the exercise-induced progressive deterioration of SR function. However, little is known about the eVect of a soccer match on SR function and the recovery of the SR system in the days after a match.…”
Section: Introductionmentioning
confidence: 70%
“…A number of studies have reported that Ca 2ϩ release from isolated SR is reduced by ϳ20 -40% following prolonged or intense exercise in humans (210,284,285) and rodents (161), although some studies found no change (111,396) or a reduction in slow-twitch but not fast-twitch muscle (161,221). It is unclear how long this effect persists after exercise, as this was only examined in one study to date, and the results were somewhat equivocal at the one recovery time examined (3.5 h) (210 ] i also greatly prolongs PCD in Xenopus fast-twitch fibers (69,70,269).…”
Section: Prolonged Reduction In Ca 2؉ Releasementioning
confidence: 99%
“…Treadmill exercise capacity has been assessed in animal models of heart failure (48, 49), diabetes (50), aging (51,52) and skeletal muscle pathophysiology (53)(54)(55)(56). Motorised rodent treadmills have been used in sepsis models though as a means of determining the impact of endurance training on outcomes (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%